Pengaruh Pengetahuan Perpajakan, Sanksi Pajak, dan Modernisasi Sistem Administrasi terhadap Kepatuhan Wajib Pajak UMKM di Kecamatan Denpasar Selatan - Putu Amanda Yadiari; An'im Falakhudin; Ni Made Sri Yadnya Wati; Baiq Aulia Sulhia (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aims to analyze the influence of tax knowledge, tax sanctions, and the modernization of administrative systems on the compliance of UMKM taxpayers in South Denpasar District. Using multiple linear regression analysis, the findings reveal that tax knowledge (β₁ = 0.421, p < 0.05) has a significant positive effect on compliance, indicating that higher literacy in tax regulations, rates, and procedures increases the likelihood of voluntary compliance. Tax sanctions (β₂ = 0.276, p < 0.05) also demonstrate a significant positive impact, supporting deterrence theory by showing that clear and consistent enforcement of penalties fosters discipline among taxpayers. Furthermore, modernization of administrative systems (β₃ = 0.389, p < 0.05), particularly through the adoption of e-filing and e-billing, significantly facilitates compliance by reducing procedural barriers and enhancing transparency. Collectively, these three variables explain 58% of the variance in taxpayer compliance, while the remaining 42% is influenced by other factors such as personal motivation, economic conditions, and cultural norms. The study underscores the importance of integrating knowledge dissemination, consistent sanction enforcement, and technological innovation to strengthen UMKM tax compliance. Practical implications are directed toward the Directorate General of Taxes in enhancing literacy programs and digital infrastructure, UMKM in improving tax awareness, and academics in exploring moderating variables to enrich future research.